Sourdough [large type] : a novel - Sloan, Robin, 1979- (Wheeler Publishing, a part of Gale, a Cengage Company, 2017)
"A new novel about an underground food community by the author of Mr. Penumbra's 24-Hour Bookstore"--!cProvided by publisher.